“Evaluación funcional, estudio y diseño definitivo de la vía la providencia cahuaji perteneciente al cantón guano, provincia de Chimborazo” - Calderón Moreno, María Estefany (2015)
The road "Providence - Cahuají" has been affected by rains constantly present during the winter season, causing floods that affect the road and around exposing the lives of the inhabitants of the area, in addition to that which does not have a drainage system for evacuation of river water.